A STUDY OF HOW STUDENTS UTILIZE WEBLOGS IN DEVELOPING WRITING SKILL - Zulfany, Dini Haiti; ., Sudarsono; Y. Sutapa, Y. Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This study sought to find out how the Fourth Semester Students of English Language Education Study Program of FKIP Untan who kept maintaining their weblogs after accomplishing Teaching Learning with ICT course use weblogs in developing writing skill. This research is a case study. Students’ experience in utilizing weblogs was elucidated with critical incident and netnography technique to find out the authenticity of students’ involvement in autonomous learning. The data derived from the questionnaires, individual in-depth interview with 7 voluntary participants, and online observation. Three themes emerged; they are blogging activities leading the students to English language learning, positive attitude toward the use of weblogs, and blogging aspects contributing in writing process approach. The findings revealed that the process of blog writing determined students’ improvement in writing skill. English language teachers are recommended to incorporate weblogs into their course syllabus to engage students in an academic atmosphere of interaction outside the classroom.   Keywords: Weblogs, writing skil, autonomous learning   Abstrak: Penelitian ini bertujuan untuk menemukan cara mahasiswa semester empat pada program studi Pendidikan Bahasa Inggris FKIP Untan yang masih mengaktifkan weblog mereka setelah menyelesaikan mata kuliah Teaching Learning with ICT memanfaatkan weblog untuk mengembangkan keterampilan menulis. Penelitian ini dilakukan dengan metode studi kasus. Pengalaman mahasiswa memanfaatkan weblog diuraikan melalui teknik critical incident dan netnography untuk mengetahui keterlibatan mahasiswa pada pembelajaran mandiri. Data diperoleh dari kuisioner, wawancara secara individu dengan 7 mahasiswa yang bersedia diwawancarai, dan melalui pengamatan online. Empat tema yang muncul dari penelitian ini yaitu aktivitas blogging yang mengarahkan siswa pada pembelajaran Bahasa Inggris, sikap positif terhadap penggunaan weblog, dan aspek-aspek blogging yang berkontribusi dalam proses menulis. Hasil penelitian menunjukkan bahwa proses ketika menghasilkan tulisan di blog berperan dalam peningkatan keterampilan menulis mahasiswa. Direkomendasikan bagi para pengajar Bahasa Inggris untuk menerapkan penggunaan weblog dalam rangka mengikutsertakan siswa pada interaksi beratmosfer akademis di luar kelas.   Kata kunci: Weblog, keterampilan menulis, pembelajaran mandiri